Case of acute kidney injury due to bilimbi fruit ingestion - Wong, Koh-Wei; Meryl Grace Lansing (BMJ Publishing Group, 2021)
Bilimbi fruit is widely eaten in Malaysia. Rarely reported is its potential to cause acute kidney injury (AKI) in patients with prior normal renal function. The possible dangers of its consumption are still relatively unknown among many. This case highlights the importance of taking a thorough dietary history in patients with AKI. We also hope to increase awareness among healthcare professionals on the nephrotoxic and neurotoxic effects of bilimbi fruits.